2004
DOI: 10.1111/j.1537-2995.2004.04019.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bacterial contamination of platelet components: six years’ experience with the BacT/ALERT system

Abstract: A screening system for detection of bacterial contamination was implemented without increase in cost owing to extension of storage time to 7 days. Transfusion of several contaminated blood components was prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
91
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 45 publications
10
91
0
2
Order By: Relevance
“…A series of studies reports on the screening results of PCs with automated culture systems [3,4,6,7,[14][15][16][17]. Comparability of the results is limited.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A series of studies reports on the screening results of PCs with automated culture systems [3,4,6,7,[14][15][16][17]. Comparability of the results is limited.…”
Section: Discussionmentioning
confidence: 99%
“…If the six cases in this study in which follow-up revealed clinical reactions following the transfusion of potentially or confirmed contaminated PCs are considered unelucidated, 80 patients remain who were transfused with potentially positive PCs and 26 patients received confirmed positive [4,6,7,14,16,17]. However, it is noteworthy that none of the six cases of mild clinical reactions in our study was reported actively but was revealed only by solicited feedback after the treating physicians had been questioned in the study follow-up by the blood service.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Screening of platelet preparations (PLTs) 2 for bacterial contamination by prospective culture testing has been implemented as part of the quality assurance program in several blood services. Despite screening of PLTs for bacterial contamination by culture, it has been demonstrated that there is still a substantial infection risk associated with transfusing PLTs, and septic complications have been observed in recipients, particularly with PLTs Ͼ4 days old (2)(3)(4)(5)(6)(7)(8)(9)(10). Early sampling strategies exhibit a high risk of sampling error, particularly when slow-growing bacteria are involved in the contamination.…”
mentioning
confidence: 99%